Foxes, voles, and waders: drivers of predator activity in wet grassland landscapes - Rebecca A. Laidlaw; Jennifer Smart; Mark A. Smart; Thomas W. Bodey; Tessa Coledale; Jennifer A. Gill (Avian Conservation and Ecology, 2019)
Impacts of generalist predators on declining prey populations are a major conservation issue, but management of this situation is constrained by limited knowledge of the factors influencing predator distribution and activity. In many declining populations of ground-nesting waders, high levels of nest and chick predation are preventing population recovery. Red foxes, Vulpes vulpes, are the main predator but their primary prey is small mammals. On wet grasslands managed for breeding waders, small mammals are concentrated in tall vegetation outside of fields, and nests closer to these patches are less likely to be predated. To assess whether these patterns result from fox attraction to small mammals, and thus the potential for management of tall vegetation to influence nest predation rates, we quantify seasonal and spatial variation in fox and small mammal activity in relation to tall vegetation patches. Across wet grassland sites, tall vegetation patches of any size (> 0.05 ha) supported small mammals and small mammal activity increased throughout the wader breeding season, while the use of fox track plots within fields declined seasonally. Although within field fox track plot use did not vary with distance to tall vegetation, over the 1064 nights of trail camera recording, foxes were seen in areas with tall vegetation on 13 nights compared with short vegetation on only two nights. These findings suggest that lower predation rates of Lapwing, Vanellus vanellus, nests close to tall vegetation could reflect fox attraction to areas with small mammal activity, but any such effects would primarily operate later in the breeding season, and may therefore primarily influence late nests and chicks.